A New Tool to Measure Malevolent Creativity: The Malevolent Creativity Behavior Scale - Hao, Ning; Tang, Mengying; Yang, Jing; Wang, Qifei; Runco, Mark A. (Frontiers in Psychology, 2016)
The present study developed the malevolent creativity behavior scale (MCBS), which contains 13 items and was designed to measure individuals’ malevolent creativity through the behavior of daily lives. A total of 958 participants from different regions of China completed the MCBS in an online fashion. Cronbach’α coefficient, using the 908 MCBSs with entirely complete data, indicated that the MCBS had satisfactory reliability. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) revealed that the MCBS had 3 dimensions: hurting people, lying, and playing tricks. MCBS scores were positively correlated with individuals’ aggression, openness, extraversion, and scores on the Runco Ideational Behavior Scale (RIBS). MCBS scores also predicted individuals’ malevolent creativity performances when solving realistic, open-ended problems. The MCBS has a simple response medium and scoring procedure. This, along with the adequate psychometric properties uncovered here, indicates that it is a useful tool for research on malevolent creativity. Given that the MCBS contains a relatively small number of categories and items, further research could expand the categories of items and develop and test more items. Moreover, it would be useful to test MCBS’s reliability and validity with other criteria. Perhaps future research could obtain actual MC data from criminal or other unambiguously malevolent samples.